2014
DOI: 10.7150/ijms.8128
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the PI3K/Akt/mTOR/p70S6K Pathway is Involved in S100A4-induced Viability and Migration in Colorectal Cancer Cells

Abstract: The S100 protein family member S100A4 regulates various cellular functions. Previous studies have shown that elevated expression of S100A4 is associated with progression and metastasis of colorectal cancer (CRC). However, little is known about whether and how S100A4 contributes to CRC development. In our present study, the elevated expression of S100A4 in CRC tissues compared to matched adjacent normal tissues was confirmed by immunohistochemistry, semi-quantitative RT-PCR and Western blot. Adenovirus-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 51 publications
(55 reference statements)
0
55
0
Order By: Relevance
“…Phosphorylated P70S6K and phosphorylated 4E-BP1 promote the translation of mRNA essential in the G1-S stage of the cell cycle and accelerate cell multiplication [6]. Now it is clear that the PI3K/AKT/mTOR/ p70S6K/4E-BP1 signaling pathway serves an important role in tumor formation, invasion, and metastasis in tumor tissue [14,15]. In the present study, our results showed that Huaier was able to inhibit the viability of tumor cells in a time-and dose-dependent manner; flow cytometry assays demonstrated that Huaier could induce cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated P70S6K and phosphorylated 4E-BP1 promote the translation of mRNA essential in the G1-S stage of the cell cycle and accelerate cell multiplication [6]. Now it is clear that the PI3K/AKT/mTOR/ p70S6K/4E-BP1 signaling pathway serves an important role in tumor formation, invasion, and metastasis in tumor tissue [14,15]. In the present study, our results showed that Huaier was able to inhibit the viability of tumor cells in a time-and dose-dependent manner; flow cytometry assays demonstrated that Huaier could induce cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperactivation of Akt/PI3K/mTOR signaling pathway by the low serum, glucose-rich and low pH growth medium stimulated nanotube formation in human malignant pleural mesothelioma (Lou et al, 2012b). This signaling pathway has a critical role in the regulation of the F-actin polymerization, the production of cellular protrusions and the cell polarization and adhesion (Rosich et al, 2014;Wang et al, 2014;Xue and Hemmings, 2013). It is known that cell polarization as well as cell adhesion is necessary to form mature and stabilize TNTs between natural killer (NK) cells and between NK cells with other cells (Chauveau et al, 2010).…”
Section: The Molecular Basis Of Tnts Formationmentioning
confidence: 98%
“…In nontransformed cells, the S100A subfamily of proteins influences calcium homeostasis, which controls cell survival, differentiation, and metabolism [45]. In the esophagus, S100A4 may contribute to the metastatic stage by inducing the phosphorylation of Akt, mTOR, and p70S6K, and by interactions with myosin IIA and various matrix metalloproteinases (MMPs) [46]. Although we did not observe metastasis at the time point assayed in our model, we did detect increased numbers of cells expressing S100A4, both at the protein (Figs 2D, 3A) and mRNA levels (Fig.…”
Section: Discussionmentioning
confidence: 99%